Theory and applications of non-integer order systems : 8th Conference on Non-integer Order Calculus and Its Applications, Zakopane, Poland - Babiarz, Artur; Czornik, Adam; Klamka, Jerzy; Niezabitowski, Michał (Springer, 2017)
This book collects papers from the 8th Conference on Non-Integer Order Calculus and Its Applications that have been held on September 20-21, 2016 in Zakopane, Poland. The preceding two conferences were held in Szczecin, Poland in 2015, and in Opole, Poland, in 2014. This conference provides a platform for academic exchange on the theory and application of fractional calculus between domestic and international universities, research institutes, corporate experts and scholars. The Proceedings of the 8th Conference on Non-Integer Order Calculus and Its Applications 2016 brings together rigorously reviewed contributions from leading international experts. The included papers cover novel various important aspects of mathematical foundations of fractional calculus, modeling and control of fractional systems as well as controllability, detectability, observability and stability problems for this systems.
Keywords: Derivatives (Mathematics) -- Congresses.; Fractional calculus -- Congresses.; elektronické knihy; electronic books